Genomic and signalling pathway characterization of the NZM panel of melanoma cell lines: A valuable model for studying the impact of genetic diversity in melanoma. (4th July 2020) - Tran, Khanh B.; Gimenez, Gregory; Tsai, Peter; Kolekar, Sharada; Rodger, Euan J.; Chatterjee, Aniruddha; Jabed, Anower; Shih, Jen‐Hsing; Joseph, Wayne R.; Marshall, Elaine S.; Wang, Qian; Print, Cristin G.; et al.
Abstract: Melanoma is a disease associated with a very high mutation burden and thus the possibility of a diverse range of oncogenic mechanisms that allow it to evade therapeutic interventions and the immune system. Here, we describe the characterization of a panel of 102 cell lines from metastatic melanomas (the NZM lines), including using whole‐exome and RNA sequencing to analyse genetic variants and gene expression changes in a subset of this panel. Lines possessing all major melanoma genotypes were identified, and hierarchical clustering of gene expression profiles revealed four broad subgroups of cell lines. Immunogenotyping identified a range of HLA haplotypes as well as expression of neoantigens and cancer–testis antigens in the lines. Together, these characteristics make the NZM panel a valuable resource for cell‐based, immunological and xenograft studies to better understand the diversity of melanoma biology and the responses of melanoma to therapeutic interventions.